2020
DOI: 10.1002/pon.5316
|View full text |Cite
|
Sign up to set email alerts
|

A self‐help intervention for reducing time to diagnosis in Indonesian women with breast cancer symptoms

Abstract: Objective: We investigated the effectiveness of a self-help intervention named PER-ANTARA, which aims to improve adherence to diagnostic procedures among women with breast cancer (BC) symptoms to reduce the time to a definitive diagnosis.Methods: With a cluster randomized crossover design across four hospitals, PER-ANTARA and treatment as usual (TAU) or TAU only was provided at successive periods in a randomly determined order. The main outcome was the time between the first medical consultation and the defini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 31 publications
0
16
0
1
Order By: Relevance
“…This may lead women with BC symptoms to be inclined to postpone or delay the timely diagnosis. Adherence to diagnostic and treatment procedures is an important public health problem, especially in low- and middle-income countries (LMICs), like Indonesia [ 13 , 14 ]. Non-adherence may negatively affect recovery and survivorship, including the risk of recurrence and mortality [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…This may lead women with BC symptoms to be inclined to postpone or delay the timely diagnosis. Adherence to diagnostic and treatment procedures is an important public health problem, especially in low- and middle-income countries (LMICs), like Indonesia [ 13 , 14 ]. Non-adherence may negatively affect recovery and survivorship, including the risk of recurrence and mortality [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…It means that out of 237 million people, there were around 237,000 breast cancer sufferers each year. Therefore, the information also showed that cancer prevalence increases with age (Setyowibowo et al, 2020).…”
Section: The 7th International Conference On Public Healthmentioning
confidence: 90%
“…Generally, breast cancer incidence reached a case, and the red incidence rate reached 58,265 cases and around 16.7% of the total cancer cases as a whole (Setyowibowo et al, 2020). It was estimated that there were 100 new cases per 100,000 population each year.…”
Section: The 7th International Conference On Public Healthmentioning
confidence: 99%
“…It consists of printed material with information about symptoms and actions to be taken and of audio-visual material with testimonials of two BC survivors. Our recent publication [9], based on data from the pre-COVID-19 period, showed that our program had a significant effect in shortening the time these women took to visit the hospital for diagnosis and treatment. The moment, however, we were planning to implement our program in the local 1 Faculty of Psychology, Universitas Padjadjaran, Jatinangor, Indonesia.…”
Section: Make Self-help Psychoeducational Programs For Breast Cancer mentioning
confidence: 99%